Effect of a high vs. standard dose of vitamin D3 supplementation on bone metabolism and kidney function in children with chronic kidney disease - Feng, Zhiqiang; Lu, Kunna; Ma, Yan; Liu, Feng; Zhang, Xinhuan; Li, Hongxiang; Fu, Yan (Frontiers in Pediatrics, 2022)
We investigated the effects of high VS. standard dose of vitamin D supplementation on kidney function and bone metabolism in children with chronic kidney disease (CKD). In all, 75 participants receive 2000 IU/D of vitamin D oral supplementation vs 75 participants who were randomized to receive 400 IU/d for a minimum of 4 months. We investigated the effects of vitamin D supplementation on kidney-related indicators and bone metabolism-related indicators at different doses. A total of 158 participants were screened and 150 met inclusion criteria. The indicators of chronic kidney disease, such as eGFR and serum uric acid, were negatively correlated with 25(OH)D levels and BMD. Serum 25(OH)D level and osteocalcin were positively correlated with spine BMD. The standard dose of vitamin D can improve serum uric acid levels, but high doses of vitamin D supplementation had no significant effect on serum uric acid. The high doses of vitamin D supplementation also improve alkaline phosphatase levels. When comparing the results of different doses of vitamin D supplementation, it was found that high-dose vitamin D supplementation did not improve bone density in the spine and femur neck relative to the standard dose of vitamin D, but improved low calciumemia and N-terminal propeptide of human procollagen type I (PINP) levels. Among the children with clinical kidney disease, treatment with Vitamin D for 4 months at a high dose, compared with a standard dose of Vitamin D treatment, resulted in statistically significantly improved kidney function but no significantly different in bone metabolism.